Perlindungan Hukum Pemegang Hak Cipta Program Komputer (Studi Kasus Putusan Nomor 60/Pdt.Sus-HakCipta/2020/PN.Niaga.Jkt.Pst) - Raden Farrel Dharma Osmar; Indah Kusuma Wardhani (Jurnal Multidisiplin Borobudur, 2023)
In this modern era, society cannot be separated from technology because they always create new creations from technology, including computer programs. However, many cases of copyright infringement on computer programs have caused losses to creators and copyright holders. Based on this, this research will analyze Decision Number 60/Pdt.SusHakCipta/2020/ PN.Niaga.Jkt.Pst. related to the legal protection of Telkom as the copyright holder of the computer program and the legal power of recording the copyright of the computer program carried out by Iman Fauzan Syarief. The research method used in this research is normative juridical. The results of the research show that Telkom has received legal protection based on Article 33 paragraph (1) jo. Article 34 jo. Article 1 point 4 of Law Number 28 of 2014 concerning Copyright because Telkom is the creator and the true Copyright holder for a computer program in the form of the CXM application. The legal power of recording Copyright on a computer program carried out by Iman Fauzan Syarief is deleted based on Article 74 paragraph (1) of Law Number 28 of 2014 concerning Copyright.